Feasibility Of Using The ‘Spacing Effect’ As Part Of An Interventional Strategy To Curb Overweight And Obesity Among Young Adults In Sungai Petani, Kedah, Malaysia - Thamby, Sam Aaseer (2018)
Overweight and obesity are defined as ‘conditions characterized by excess body fat with negative health consequences’. The numbers of overweight and obese individuals are on the rise in Malaysia, despite numerous attempts by means of public health campaigns. This epidemic has affected a very high number of young adults, aged between 18 to 30 years old. Interventions aimed at educating the public about the negative health impact of being overweight and/or obese were not entirely successful in combating this issue. This exploratory, prospective, and descriptive study was conducted among a representative sample of overweight and obese individuals in Sungai Petani.